One map policy as an anti-corruption endeavour in the Indonesian mining sector - Muhammad Arief Virgy; Mustabsyirotul Ummah Mustofa; Ahmad Mikail (Komisi Pemberantasan Korupsi, 2024)
Indonesia plays an important role in the global mining industry, particularly in coal and nickel. Ensuring that mining resources support the people's livelihoods, as mandated by the 1945 Constitution of the Republic of Indonesia, requires good governance in the mining sector. However, corruption remains a significant challenge. This research identifies the types of corruption present in the mining sector and proposes solutions. Using qualitative methods and collecting secondary data sources such as news reports and other accessible documents, the study reveals that corruption mostly occurs in the issuance of mining permits, often due to overlapping areas between mining permits and other land uses. In order to address these issues and strengthen governance, the One Map Policy has been proposed. This policy aims to improve spatial planning quality, reduce overlaps between mining concessions and Indigenous peoples’ areas, and prevent concessions in protected forests. However, the policy faces challenges due to a lack of transparency in making map data publicly accessible, which hinders external inputs. Additionally, there is no government body responsible for verifying independent map data from external sources. Enhancing transparency and involving external parties in providing input to the One Map Policy can promote accountability, ensuring mining activities adhere to good governance principles and protect local communities and Indigenous peoples’ rights as well as their livelihoods.